The genus Campylobacter: detection and isolation methods, species identification & typing techniques - NATSOS, G.; MOUTTOTOU, N. K.; AHMAD, S.; KAMRAN, Z.; IOANNIDIS, A.; KOUTOULIS, K. C. (Journal of the Hellenic Veterinary Medical Society, 2019)
Campylobacter is well recognized as the leading cause of bacterial foodborne diarrheal disease worldwide; while, poultry has been identified as a significant cause of campylobacter infection in humans. The C. jejuni has been found to be the predominant species isolated from poultry samples and, yet, responsible for the majority of human campylobacteriosis. Campylobacter spp. are small, oxidase positive, microaerophilic, curved gram-negative rods exhibiting corkscrew motility and colonize the intestinal tract of most mammalian and avian species. From its very first description in late 19th century by Theodor Escherich until nowadays, a lot of research has been carried out providing a wealth of information regarding its microbiological properties. Since novel technologies constantly emerge, increasingly advanced methods for detection, identification and typing of Campylobacter spp. are becoming available. The aim of this article is to review the recent bibliography on Campylobacter focusing, especially, on its survival and growth characteristics, the laboratory methods used for its detection and isolation from clinical, animal, environmental, and food samples, the reported methods applied for its speciation, as well as the typing systems developed for subtyping of Campylobacter.